Performa Desa yang Diusulkan untuk Penerapan One Village One Product (OVOP) di Kabupaten Pamekasan - Farahdilla Kutsiyah (Institut Agama Islam Negeri Madura, 2017)
“One village, one product” (OVOP) is an approach to rural development by using local resources which aim to enrich local wisdom and led to the enlargement of small and medium industry. This research uses an exploratory study to describe the village performance that was suggested for OVOP application in Pamekasan regency. Observation and interview was applicated in collected data. The results of this study are a good quality for OVOP operation village: Bangsereh, Dempo Barat, Polagan, Kadur, Blumbungan, Pegagan, Rekkerrek, Tebul Barat, Klampar /Toket, Kertagena Laok, Larangan Slampar, Sokalelah and Pegantenan villages. The recommended commodity in each village sequentially onion, Madura beef cattle, anchovies anvil, hybrid corn, java long pepper, mangrove, cassava, ginger, batik, seaweed, laying hens, great chili, banana and durian. This area have more superiority and special characteristic in a production, uniqueness, institutional and human resources. Therefore their development must be adapted to the potential of the region, local wisdom and limiting factor. Meanwhile the main issue for expansion of these commodities are lack of product processing, capital and marketing. Moreover inefficient of institutional and unsustainability of production as well as minimize of assistance for human resource investment. It is suggested to support OVOP implementation, it is necessary to integrate of all relevant institutions, which each of them do as their self-capacity into a straight planning, to built a cooperative institution, to create the government policies by prioritize the processing and lead this area as a village industry. Furthermore, facilitated marketing product, intensified of extension and advisory group institution for community and also directed to have the village market.